Guns, germs, and steel [compact disc, unabridged] : the fates of human societies - Diamond, Jared M. (Random House Audio, 1999)
Jared Diamond, Professor of Physiology at the UCLA School of Medicine, goes beyond weapons, war tactics, and politics to show how biological and environmental factors changed and shaped thousands of years of history.